2010
DOI: 10.1007/s00705-010-0612-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SARS-like coronaviruses in horseshoe bats (Rhinolophus hipposideros) in Slovenia

Abstract: Bats have been identified as a natural reservoir for an increasing number of emerging zoonotic viruses, such as Hendra virus, Nipah virus, Ebola virus, Marburg virus, rabies and other lyssaviruses. Recently, a large number of viruses closely related to members of the genus Coronavirus have been associated with severe acute respiratory syndrome (SARS) and detected in bat species. In this study, samples were collected from 106 live bats of seven different bat species from 27 different locations in Slovenia. Coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
88
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 50 publications
8
88
1
Order By: Relevance
“…Up to present, bat SARSr-CoVs have been discovered in Asia, Europe and Africa (Balboni et al, 2012b;Drexler et al, 2010;He et al, 2014;Lau et al, 2010Lau et al, , 2005Li et al, 2005;Ren et al, 2006;Rihtaric et al, 2010;Yang et al, 2013;Yuan et al, 2010). However, for most of these strains from countries other than China, only partial RdRp fragment were obtained and full-length genome sequences have been determined for only few of them, thus the available genetic information is insufficient to explore the evolution and spread of these SARSr-CoVs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to present, bat SARSr-CoVs have been discovered in Asia, Europe and Africa (Balboni et al, 2012b;Drexler et al, 2010;He et al, 2014;Lau et al, 2010Lau et al, , 2005Li et al, 2005;Ren et al, 2006;Rihtaric et al, 2010;Yang et al, 2013;Yuan et al, 2010). However, for most of these strains from countries other than China, only partial RdRp fragment were obtained and full-length genome sequences have been determined for only few of them, thus the available genetic information is insufficient to explore the evolution and spread of these SARSr-CoVs.…”
Section: Discussionmentioning
confidence: 99%
“…In 2005, the discovery of novel CoVs related to human SARS-CoVs in Chinese horseshoe bats (genus Rhinolophus), named SARS-related coronaviruses (SARSr-CoVs), provided new clue that bats may be the natural host for SARS-CoV (Lau et al, 2005;Li et al, 2005). Since then, genetically diverse SARSr-CoVs have been discovered in Asia, Europe, and Africa, including China, South Korea, Thailand, Bulgaria, Slovenia, Italy, Luxembourg, Nigeria, and Kenya (Balboni et al, 2012b;Drexler et al, 2010;He et al, 2014;Lau et al, 2010;Lau et al, 2005;Li et al, 2005;Pauly et al, 2017;Ren et al, 2006;Rihtaric et al, 2010;Yang et al, 2013;Yuan et al, 2010). Importantly, it was reported that some bat SARSr-CoVs were able to use angiotensin converting enzyme II (ACE2) from humans, civets and Chinese horseshoe bats as a receptor originated from Chinese horseshoe bats and suggesting that these SARSr-CoVs had the ability to infect humans immediately without other intermediate hosts.…”
Section: Discovery Of Bat Sars-related Coronaviruses (Sarsr-covs)mentioning
confidence: 99%
“…Values at deep nodes indicate statistical support from Bayesian posterior probabilities, scale bar genetic distance. or potentially civets (Balboni et al, 2011;Drexler et al, 2010;Lau et al, 2010aLau et al, , 2005Li et al, 2005;Ren et al, 2006;Rihtaric et al, 2010;Yang et al, 2013). These human, civet and bat viruses are now officially summarized by the ICTV in one species, termed SARS-related coronavirus (de Groot et al, 2012).…”
Section: Evidence For Phylogenetic Co-segregation Of Coronaviruses Anmentioning
confidence: 99%
“…The etiological agent of this disease was found to be a previously unknown coronavirus (SARS-CoV) Fouchier et al, 2003;Ksiazek et al, 2003;Lee et al, 2003;Peiris et al, 2003;Rota et al, 2003). In the last years SARS-CoV like viruses have been found circulating in bats from several continents (Drexler et al, 2010;Lau et al, 2005;Quan et al, 2010;Rihtaric et al, 2010) and bats have been described as putative reservoirs of SARS-CoV (Calisher et al, 2006;Li et al, 2005). Thus, the possibility of SARS reoccurrence remains.…”
mentioning
confidence: 99%